The use of the strength and difficulties questionnaire in psychosocial evaluation and attention deficit hyperactivity disorder screening in preterm infants - Luis Bachiller-Carnicero; Carmen Elia García-Soria; Salvador Piris-Borregas; Purificación Sierra-García; María José Torres-Valdivieso; Carmen Rosa Pallás-Alonso (Elsevier, 2019)
Introduction: Behavioural disorders and learning disabilities are often recognised in <1500 g or <32 weeks very low birth weight (VLBW) infants. There is very limited data in the Spanish population. Objective: To determine the presence of psychosocial disorders in preterm infants at 6 years of age, as assessed by the strength and difficulties (SDQ) questionnaire, in comparison to a reference population. To set a cut-off value to use SDQ as a screening tool for attention deficit hyperactivity disorder (ADHD) in the preterm child. Participants and methods: A prospective observational study was conducted on premature children assessed at 6 years of age using the SDQ. Perinatal variables, neurodevelopment, and diagnosis of ADHD, according to the DSM-5, were collected. Results: A total of 214 children who met all the requirements, were included. When compared with the reference population they had significantly higher scores in emotional symptoms, in peer relationships, and in the total score of the test. The hyperactivity scale and the total test score are good predictors of a diagnosis of ADHD, with an area under the ROC curve of 0.83 (95% CI: 0.76-0.90) for hyperactivity, and 0.87 (95% CI: 0.80-0.93) for the total score. The scores for hyperactivity and the total test, from which the screening for ADHD could be considered positive would be ≥6 and ≥13 respectively, and a combination of hyperactivity ≥5 and total score ≥12. Conclusions: Preterm children are at higher risk of emotional and peer relationship problems than those born full term. The SDQ test could be used for ADHD screening. Resumen: Introducción: Los trastornos del comportamiento y del aprendizaje se describen con frecuencia en <1.500 g o <32 semanas (RNMBP/MP). Se dispone de muy poca información en población española. Objetivo: Identificar los problemas psicosociales de los RNMBP/MP mediante la aplicación del test Strength and Difficulties Questionnaire (SDQ) a los 6 años y comparar los resultados con los de una población de referencia. Establecer los puntos de corte para el uso del SDQ como cribado del trastorno por déficit de atención e hiperactividad (TDAH) en RNMBP/MP. Participantes y métodos: Estudio prospectivo observacional en RNMBP/MP evaluados a los 6 años con SDQ. Se recogen variables perinatales, neurodesarrollo y diagnóstico de TDAH mediante DSM-5. Resultados: Se incluyeron 214 niños con el total de las valoraciones. Comparados con la población de referencia obtuvieron puntuaciones significativamente mayores en síntomas emocionales, relaciones con compañeros y en el total del test. La escala de hiperactividad y la puntuación total se identifican como buenos predictores del diagnóstico de TDAH, con un área bajo la curva ROC de 0,83 y 0,87, respectivamente. Las puntuaciones que consiguen una adecuada sensibilidad para el cribado de TDAH son ≥6 para la escala de hiperactividad y ≥13 para la puntuación total del test, y una puntuación combinada ≥5 en hiperactividad junto con un total ≥12. Conclusiones: Los RNMBP/MP presentan más frecuentemente problemas emocionales y de relación que sus compañeros nacidos a término. El test SDQ podría utilizarse como una prueba de cribado para el TDAH.